Pengaruh Metode Student Facilitator And Explaning Terhadap Hasil Belajar Sosiologi Siswa Kelas XI SMA Kartika Ambon - Lamberthus. J. Lokollo; Ferdinanda S. Noya (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the effect of the Student Facilitator and Explaining learning method on the sociology learning outcomes of class XI students at SMA Kartika Ambon. This research uses a quasi-experimental research design. The research subjects were 25 students of class XI IPS SMA Kartika Ambon. The results of this research show that there is an influence of the use of the Student Facilitator And Explaining learning method on the learning outcomes of class (2-tailed) of 0.000 < 0.05, and the experimental class obtained an average N-Gain value of 68.11, including the Fairly Effective category, so it can be concluded that H0 is rejected and H1 is accepted, because the significant value is smaller than 0 .05. So, there is an influence of applying the Student Facilitator And Explaining learning method on student learning outcomes. It is hoped that school principals will continue to provide direction to teachers in providing policies to develop learning, teachers are expected to master various learning methods so that they can improve student learning outcomes, and students are expected to always pay attention to teachers and play an active role in learning